2021
DOI: 10.1002/adhm.202100482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrophobicity on Antimicrobial Activity, Selectivity, and Functional Mechanism of Guanidinium‐Functionalized Polymers

Abstract: In this study, a series of guanidinium-functionalized polycarbonate random co-polymers is prepared from organocatalytic ring-opening polymerization to investigate the effect of the hydrophobic side chain (ethyl, propyl, isopropyl, benzyl, and hexyl) on their antimicrobial activity and selectivity. Although the polymers exhibit similar minimum inhibitory concentrations, the more hydrophobic polymers exhibit a faster rate of bacteria elimination. At higher percentage content (20 mol%), polymers with more hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…The observed effect may be related to aggregation of C8‐ and C12‐ionenes, proved by CAC measurements (Table 1), or a detergent‐like mechanism executed on the lipid bilayer. [ 76 ] Selectivity index (SI) of the ionenes toward microorganisms over RBCs, defined as HC 50 /MIC, drops sharply with the alkyl group elongation above C4 (Table 2). Such an impact of the hydrophobicity on SI of SMAMPs and AMPs was already reported by other researcher.…”
Section: Resultsmentioning
confidence: 99%
“…The observed effect may be related to aggregation of C8‐ and C12‐ionenes, proved by CAC measurements (Table 1), or a detergent‐like mechanism executed on the lipid bilayer. [ 76 ] Selectivity index (SI) of the ionenes toward microorganisms over RBCs, defined as HC 50 /MIC, drops sharply with the alkyl group elongation above C4 (Table 2). Such an impact of the hydrophobicity on SI of SMAMPs and AMPs was already reported by other researcher.…”
Section: Resultsmentioning
confidence: 99%
“…The main purpose of this work was to better understand how the hydrophilicity/hydrophobicity ratio of an antimicrobial compound may affect its effect. It is well known that the antimicrobial efficacy of cationic polymers can be improved by increasing their hydrophobicity [35]. The antimicrobial results presented here are compared to previous published work, where similar copolymers bearing more hydrophobic aliphatic chains with 16-carbon atoms were studied [27,28].…”
Section: Antimicrobial Activity Of the Polymeric Materialsmentioning
confidence: 90%
“…This phenomenon was also observed in other polymer systems. [15] The relatively more hydrophobic polyionenes might interact with the proteins present in the culture medium, masking their antimicrobial activity. Consistently, we observed that media containing polyionenes X1, X2, Y, Z1, Z2, and Z3 were cloudier with micrometer-sized aggregates than that of polyionenes A-E especially at high concentrations.…”
Section: Discussionmentioning
confidence: 99%